Risk of gynecomastia and breast cancer associated with the use of 5-alpha reductase inhibitors for benign prostatic hyperplasia - Hagberg, Katrina Wilcox (Clin Epidemiol, 2017)
BACKGROUND: Clinical trial results suggest that 5-alpha reductase inhibitors (5ARIs) for the treatment of benign prostatic hyperplasia (BPH) may increase the risk of gynecomastia and male breast cancer, but epidemiological studies have been limited. PATIENTS AND METHODS: We conducted a cohort study with nested case–control analyses using the UK Clinical Practice Research Datalink. We identified men diagnosed with BPH who were free from Klinefelter syndrome, prostate, genital or urinary cancer, prostatectomy or orchiectomy, or evidence of gynecomastia or breast cancer. Patients entered the cohort at age ≥40 years and at least 3 years after the start of their electronic medical record. We classified exposure as 5ARIs (alone or in combination with alpha blockers [ABs]), AB only, or unexposed to 5ARIs and ABs. Cases were men who had a first-time diagnosis of gynecomastia or breast cancer. Incidence rates and incidence rate ratios (IRRs) with 95% confidence intervals (CIs) in the gynecomastia analysis and crude and adjusted odds ratios (ORs) with 95% CIs in both analyses were calculated. RESULTS: Compared to no exposure, gynecomastia risk was elevated for users of 5ARIs (alone or in combination with ABs) in both the cohort (IRR=3.55, 95% CI 3.05–4.14) and case–control analyses (OR=3.31, 95% CI 2.66–4.10), whereas the risk was null for users of AB only. The increased risk of gynecomastia with the use of 5ARIs persisted regardless of the number of prescriptions, exposure timing, and presence or absence of concomitant prescriptions for drugs known to be associated with gynecomastia. The risk was higher for dutasteride than for finasteride. 5ARI users did not have an increased risk of breast cancer compared to unexposed men (OR=1.52, 95% CI 0.61–3.80). CONCLUSION: In men with BPH, 5ARIs significantly increased the risk of gynecomastia, but not breast cancer, compared to AB use and no exposure.